(untitled) (Tanzania Medical Journal, 2020)
Background: The incidence of prostate cancer in Tanzania is among the highest recorded in Africa. Prostate cancer is also the most common cancer among men aged 50 years and above in Tanzania. Our study aimed to determine the awareness, knowledge, and attitudes among adult men with age 50 years and above regarding prostate cancer. Methods: This was a cross-sectional study that included 250 adult men aged 50 years and above in Lindi municipal being purposively selected and we interviewed them by using a structured questionnaire. A stratified random sampling method was used for obtaining our participants. All men who had stayed for not less than one year in Lindi and willing to participate were enrolled in the study. These men were selected at households without screening whether or not they had taken prostate screening test or had been diagnosed with prostate cancer Quantitative data were cleaned and analyzed with SPSS version 20. Results: Majority, 216(86.7%) of our study participants were aged 50–69 years and most of them, 142(56.8%) had primary education with 93.2% of them being married. Among the study subjects 7.2% had positive family history of cancer and 195(78%) were aware of prostate cancer with source of information being mass media (62.6%). Majority of them, 63.2%, did not know the risk age group. Few, 20.8% of our participants had good knowledge while majority, 95.2% had negative attitude toward prostate cancer. We found a statistically significant association between level of education, family history and level of knowledge regarding prostate cancer with p < 0.005. Conclusion: This study revealed high level of awareness, but poor knowledge regarding prostate cancer and negative attitude toward prostate cancer among men with age ?50 years in Lindi municipal Tanzania. Key words: Awareness, knowledge, attitude, prostate cancer.